2024
DOI: 10.3390/land13030399
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Sensitivity of Phenology to Seasonal Climate Differences in Temperate Grasslands of China Based on Normalized Difference Vegetation Index

Xiaoshuai Wei,
Mingze Xu,
Hongxian Zhao
et al.

Abstract: The affiliation between vegetation phenology and seasonal climate (start and end times of the growing season, or SOS and EOS) provides a basis for acquiring insight into the dynamic response of terrestrial ecosystems to the effects of climate change. Although climate warming is an important factor affecting the advancement or delay of plant phenology, understanding the sensitivity of phenology to seasonal variation in climate factors (e.g., local air temperature, precipitation) is generally lacking under diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
(102 reference statements)
0
0
1
Order By: Relevance
“…Consequently, the impact of summer sunlight duration on the yellowing phase of grasslands was greater than that of autumn. In investigating the phenology of temperate grasslands in China, Wei et al observed that an increase in autumn temperatures, particularly in regions with temperatures between • C and −5 • C, tends to delay the EOS [76]. On the contrary, our findings from Xinjiang suggest an opposite trend, where warmer autumn temperatures accelerate the EOS.…”
Section: Significant Impact Of Seasonal Climatic Factors On Grassland...contrasting
confidence: 79%
“…Consequently, the impact of summer sunlight duration on the yellowing phase of grasslands was greater than that of autumn. In investigating the phenology of temperate grasslands in China, Wei et al observed that an increase in autumn temperatures, particularly in regions with temperatures between • C and −5 • C, tends to delay the EOS [76]. On the contrary, our findings from Xinjiang suggest an opposite trend, where warmer autumn temperatures accelerate the EOS.…”
Section: Significant Impact Of Seasonal Climatic Factors On Grassland...contrasting
confidence: 79%